Peptides in Receptor-Mediated Radiotherapy: From Design to the Clinical Application in Cancers - LOZZA, Catherine; TEULON, Isabelle; PELEGRIN, André; POUGET, Jean-Pierre; VIVES, Eric (Frontiers in Oncology, 2013)
Short peptides can show high affinity for specific receptors overexpressed on tumor cells. Some of these are already used in cancerology as diagnostic tools and others are in clinical trials for therapeutic applications. Therefore, peptides exhibit great potential as a diagnostic tool but also as an alternative or an additional antitumoral approach upon the covalent attachment of a therapeutic moiety such as a radionuclide or a cytotoxic drug. The chemistry offers flexibility to graft onto the targeting peptide either fluorine or iodine directly, or metallic radionuclides through appropriate chelating agent. Since short peptides are straightforward to synthesize, there is an opportunity to further improve existing peptides or to design new ones for clinical applications. However, several considerations have to be taken into account to optimize the recognition properties of the targeting peptide to its receptor, to improve its stability in the biological fluids and its residence in the body, or to increase its overall therapeutic effect. In this review, we highlight the different aspects which need to be considered for the development of an efficient peptide receptor-mediated radionuclide therapy in different neoplasms.